Heterogeneity in diagnostic characters across ecoregions: A case study with Botrynema (Hydrozoa: Trachylina: Halicreatidae) - Montenegro, Javier; Collins, Allen G.; Hopcroft, Russell R.; Questel, Jennifer M.; Thuesen, Erik V.; Bachtel, Tiffany S.; Bergman, Leah A.; Sangekar, Mehul N.; Drazen, Jeffrey C.; Lindsay, Dhugal J. (Frontiers in Marine Science, 2023)
Introduction Botrynema, a genus of medusozoans in the trachyline family Halicreatidae, currently contains two species: B. brucei and B. ellinorae, distinguished by the presence or absence, respectively, of an apical knob as a diagnostic character. However, no study has corroborated if these taxonomic diagnoses have a biological and evolutionary basis. Therefore, in this study we attempted to address the question “do the two nominal species in the genus Botrynema represent independent phylogenetic lineages, or two phenotypic variants of a single species? Methods In this study we took advantage of legacy collections from different research expeditions across the globe from 2000 to 2021 to study the phylogenetics and taxonomy of the genus Botrynema. Results B. brucei and B. ellinorae present partially overlapping vertical distributions in the Arctic and as a whole in the Arctic the genus seems to be limited to the Atlantic water masses. The phylogenetic reconstruction based on the concatenated alignment corroborates the validity of the family Halicreatidae and of genus Botrynema as monophyletic groups. However no clear differentiation was found between the two presently accepted species, B. ellinorae and B. brucei. Discussion Based on the evidence we gathered, we conclude that while the genus Botrynema does contain at least two species lineages, these lineages are not concordant with current species definitions. The species B. ellinorae is reassigned as a subspecies of B. brucei and diagnostic characters are provided.